Reflections on the State of Multicultural Education in Historically White South African Schools - Alexander, Gregg (Kamla-Raj: International Journal of Educational Sciences, 2016)
The first South African democratic elections ushered in a new schooling system that was previously fragmented along racial and ethnic lines, unequal access to education and inequality. Post Apartheid policy developments, transformational imperatives and social changes, prone on promoting democracy, human dignity equality and social justice become the cornerstone for a new dispensation, particularly a non-racial, desegregated, multicultural schooling system. Twenty years after the abolished of Apartheid, it is observed via media reports and journal articles that incidences of racism, prejudice and human rights violence are still rife in these supposedly multicultural institutions. The purpose of this paper is therefor to reflect critically, through a qualitative study, on the state of multicultural education in historically White schools of South Africa. A key finding revealed that historically White schools have different notions and uphold various practices confined to multicultural education.
Published Article
Keywords: Desegregation; Integrated Schools; Post-apartheid South Africa; Segregated Schooling System